Knowledge, attitude, and perception towards COVID-19 vaccinations among the adults in Rwanda: a cross-sectional study - Abakundana Nsenga Ariston Gabriel; Xiao-Yang Wang; Laila Jamil; Mulugeta Shegaze Shimbre; Gerard Bikorimana; Lin Zhao; Wu-Chun Cao (BMC, 2024)
Abstract Background Multiple vaccinations have received approval for the prevention of the coronavirus illness. Nevertheless, the sluggish vaccination rate is mostly attributed to the general population's limited understanding and unwillingness to accept the use of vaccinations. Thus, it is important to investigate the Rwandan population's knowledge, attitudes, and perceptions toward COVID-19 vaccines. Methods A cross-sectional survey was conducted among 370 participants from 11th to 17th February 2023. Demographic information was gathered, and knowledge, attitudes, and perceptions of COVID-19 vaccinations were assessed. A binary logistic regression analysis was undertaken to determine the parameters that determine the perception of COVID-19 vaccinations. Results This study included 370 participants. Among them, 85% had good knowledge about COVID-19 vaccines, and 84% had a positive attitude towards them. Additionally, the study had a diverse group, with half of the participants being female and nearly half falling between the ages of 30 and 39. Several key findings emerged through logistic regression analysis. Those aged 30-39 had 1.39 times higher odds of positive perception than 18-28 (OR = 1.39, 95% CI = 1.08-3.24). Participants with a university education were twice as likely to have a positive perception compared to those without an education level (OR = 2.43, 95% CI = 1.30-6.20). Additionally, single individuals were three times more likely to have a positive perception than their married counterparts (OR = 3.39, 95% CI = 1.28-9.09). Vaccinated individuals had twice the odds of positive perception than non-vaccinated individuals (OR = 2.89, 95% CI = 1.01-8.89). Those receiving information from government health institutions were three times more likely to have a positive perception than those who received the information from friends (OR = 3.19, 95% CI = 1.02-12.7). Moreover, employed participants were four times more likely to have a positive perception non-employed individuals (OR = 4.21, 95% CI = 1.48-13.6). Besides, gender and COVID-19 diagnosis did not significantly correlate with positive COVID-19 vaccine perception. Conclusion The results indicate that the general public in Rwanda has good knowledge, positive attitudes, and a positive perception toward the COVID-19 vaccination, however, some of the participants had some misconceptions towards COVID-19. The findings of this study will be valuable for policymakers and healthcare authorities working to improve vaccination rates.